Olive Kitteridge [videorecording (DVD)] - McDormand, Frances; Jenkins, Richard, 1947-; Gallagher, John, Jr., 1984-; Strout, Elizabeth ([Publisher not identified], 2015)
The four-part drama tells the story of a seemingly placid New England town wrought with illicit affairs, crime and tragedy, told through the lens of Olive, whose wicked wit and harsh demeanor mask a warm but troubled heart and staunch moral center.